Political risk spreads - Bekaert, Geert; Harvey, Campbell R; Lundblad, Christian T; Siegel, Stephan (Journal of International Business Studies, 2014)
We introduce a new, market-based and forward-looking measure of political risk derived from the yield spread between a country’s US dollar debt and an equivalent US Treasury bond. We explain the variation in these sovereign spreads with four factors: global economic conditions, country-specific economic factors, liquidity of the country’s bond, and political risk. We then extract the part of the sovereign spread that is due to political risk, making use of political risk ratings. In addition, we provide new evidence that these political risk ratings are predictive, on average, of future risk realizations using data on political risk claims as well as a novel textual-based database of risk realizations. Our political risk spread measure does not make the mistake of double counting systematic risk in the evaluation of international investments, as some conventional measures do. Furthermore, we show how to construct political risk spreads for countries that do not have sovereign bond data. Finally, we link our political risk spreads to foreign direct investment (FDI). We show that a 1% point reduction in the political risk spreads is associated with a 12% increase in net-inflows of FDI.